IDENTIFIKASI JENIS TUTUPAN LAHAN DI KAWASAN KPHP POIGAR DENGAN METODE MAXIMUM LIKELIHOOD - Abdul M. Muhammad; Johan A. Rombang; Fabiola B. Saroinsong (COCOS, 2016)
ABSTRACTLand cover of KPHP Poigar constantly has been changing. Mapping and identification by Maximum Likelihood method was more accurate than another method. Purpose of this research is to analyze the capability Maximum Likelihood Classification to map and identify the type of land cover in KHPH Poigar area. This research was carried out in September – November 2015 and in four steps. The first step was Image Pre-processing such a Layer Stacking process. Second step consists of OIF (Optimum Index Factor) Calculation, Cropping, and Visual Image Interpretation. Third step was Ground check in KPHP Poigar area. Fourth step were Image Analyzing with Maximum Likelihood Classification method and Accuracy Test. The value of accurate test for Overall Accuracy (OA) was 85,04 percent and for Kappa Accuracy (KA) was 80,97 percent classified into Almost Perfect Agreement category. The result of land cover classification based on image analyzing with Maximum Likelihood Classification method in KHPH Poigar indicated that there are 5 types of land cover, they are forest (21597,21 ha), bareland (5799,69 ha), bush (5612,58 ha), farmland (5649,12 ha) and mixed farmland (2942,37 ha).Keywords : Maximum Likelihood, KPHP Poigar, Type of Land Cover, Accuracy